2017
DOI: 10.3892/ijo.2017.4039
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 acetylation prevents caspase-dependent/independent apoptosis and autophagic cell death in cancer cells

Abstract: Cancer cells are continuously challenged by adverse environmental factors including hypoxia, metabolite restriction, and immune reactions, and must adopt diverse strategies to survive. Heat shock protein (Hsp) 70 plays a central role in protection against stress-induced cell death by maintaining protein homeostasis and interfering with the process of programmed cell death. Recent findings have suggested that Hsp70 acetylation is a key regulatory modification required for its chaperone activity, but its relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 30 publications
0
19
1
Order By: Relevance
“…Our findings suggested that EFEN treatment up-regulated CDC2/cyclin B levels and further induced G2/M arrest and that EFEN induced apoptosis by up-regulating Bcl-2/Bax ration and activating caspase-3, -8 and -9. Thus, EFEN induced apoptosis through diverse caspase-dependent pathways (Park et al., 2017 ). More work should be done to classify in more detail the apoptotic pathways involved.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings suggested that EFEN treatment up-regulated CDC2/cyclin B levels and further induced G2/M arrest and that EFEN induced apoptosis by up-regulating Bcl-2/Bax ration and activating caspase-3, -8 and -9. Thus, EFEN induced apoptosis through diverse caspase-dependent pathways (Park et al., 2017 ). More work should be done to classify in more detail the apoptotic pathways involved.…”
Section: Resultsmentioning
confidence: 99%
“…As we all known, HSP70 was a member of heat shock protein molecular chaperone family. 45,46 HSP70 played a central role in protection against stress-induced cell death. Therefore, we further studied the effect of HSP70 on apoptosis.…”
Section: Hsp70 Inhibited Apoptosis In Vecs Deprived Of Serum and Fgf-2mentioning
confidence: 99%
“…This indicates a role of HSF1 in histone acetylation control during heat stress. HSP70 acetylation can also protect stressed cells inhibiting cell death through association with apoptotic protease‐activating factor (APAF)‐1 (Caspase‐dependent cell death) and apoptosis‐inducing factor (AIF; caspase‐independent cell death; Candé et al, ; Y. H. Park, Seo, Park, Lee, & Kim, ; Ravagnan et al, ; Saleh, Srinivasula, Balkir, Robbins, & Alnemri, ). The balance between protein refolding and degradation in response to stress is regulated by acetyltransferase arrest defective 1 mediated HSP70 acetylation (Seo et al, ).…”
Section: Heat‐induced Epigenetic Changes In Early Embryonic Developmentmentioning
confidence: 99%